1985
DOI: 10.1002/1097-0142(19851101)56:9<2155::aid-cncr2820560903>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of doxorubicin versus doxorubicin plus cisplatin in patients with advanced thyroid carcinoma

Abstract: A randomized evaluation of the effectiveness and toxicity of the combination of doxorubicin and cisplatin and of doxorubicin alone in patients with advanced thyroid carcinoma was carried out. Ninety-two patients were entered and 84 were evaluable. They were stratified according to histological classification, Eastern Cooperative Oncology Group (ECOG) performance status, and metastatic sites. Forty-one patients received doxorubicin as a single agent and seven had partial response (17%). Forty-three patients rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
180
0
7

Year Published

1988
1988
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 435 publications
(191 citation statements)
references
References 5 publications
4
180
0
7
Order By: Relevance
“…The 10-year survival rate is less than 15% (6, 7). Doxorubicin is the only U.S. Food and Drug Administration–approved therapy but is generally considered of low efficacy and high toxicity (8, 9). …”
Section: Introductionmentioning
confidence: 99%
“…The 10-year survival rate is less than 15% (6, 7). Doxorubicin is the only U.S. Food and Drug Administration–approved therapy but is generally considered of low efficacy and high toxicity (8, 9). …”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have reported that single-agent doxorubicin has a response rate of 25-40 % and is the most effective chemotherapeutic agent. Also, there is little evidence to suggest that combination chemotherapy is more effective [19][20][21]. Therefore, the development of novel therapies, such as biological modifiers or new chemotherapy agents, is urgently needed for this disease.…”
Section: Discussionmentioning
confidence: 99%
“…In the Eastern Cooperative Oncology Group trial of doxorubicin-containing regimens, PFS time for patients with metastatic iodine non-avid differentiated thyroid cancer was estimated at 2 months for both doxorubicin alone and doxorubicin plus cisplatin, and median overall survival time was 8 months (29). In the present study, we observed a median PFS of 26.5 months, which might represent a considerably significant improvement in the outcome of these patients.…”
Section: Discussionmentioning
confidence: 99%